1998
DOI: 10.4269/ajtmh.1998.58.824
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous scars in American tegumentary leishmaniasis patients: a site of Leishmania (Viannia) braziliensis persistence and viability eleven years after antimonial therapy and clinical cure.

Abstract: Two former patients treated for the cutaneous form of American tegumentary leishmaniasis were reviewed eight and 11 years, respectively, following clinical cure. We were able to isolate Leishmania parasites in a culture of material from the two scar biopsies, and in one of them the parasite was characterized as Leishmania (Viannia) braziliensis. In both cases, the histopathology revealed discreet hyperceratosis and a slight infiltrate of mononuclear cells surrounding and on the walls of the surface and deep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 32 publications
(46 reference statements)
3
65
0
7
Order By: Relevance
“…It is likely that there is a dynamic and intense process of amastigotes destruction and subsequent antigen processing in active lesions, while in scars, the antigen keep still linked to phagocitic mononuclear cells or endothelial cells for many years after healing. Alternatively, as suggested by the finding of positive cultures in CL scars, there could be a state of equilibrium between host and parasite in which a light inflammatory response would allow survival of amastigotes sufficient to sustain the process (Müller 1992, Schubach et al 1998b. Others papers reinforce this view , Stenger et al 1996, Bogdan & Röllinghoff 1998.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is likely that there is a dynamic and intense process of amastigotes destruction and subsequent antigen processing in active lesions, while in scars, the antigen keep still linked to phagocitic mononuclear cells or endothelial cells for many years after healing. Alternatively, as suggested by the finding of positive cultures in CL scars, there could be a state of equilibrium between host and parasite in which a light inflammatory response would allow survival of amastigotes sufficient to sustain the process (Müller 1992, Schubach et al 1998b. Others papers reinforce this view , Stenger et al 1996, Bogdan & Röllinghoff 1998.…”
Section: Discussionmentioning
confidence: 75%
“…Beside the finding of 2 (5.7%) positive cultures in Group II (Schubach et al 1998b), persistence of parasite antigen was demonstrated in 21 (60%) out of 35 CL scars (Group II) and in 4 (66.6%) out of 6 suspected scars of MCL (Group III). In another study (Schubach et al 1998a) 10 patients of Group I were included.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals, even in spite of treatment and aparent cure of the disease, Leishmania parasites can persist and reactivate (Saravia et al 1990, Guevara et al 1993, Aebischer 1994, Schubach et al 1998) raising the question on molecular determinants of virulence in some parasite strains. No relapse of the symptoms was observed in our immunocompromised patient over a period of two years.…”
Section: Discussionmentioning
confidence: 99%
“…UAW bei Antimonen treten häufiger bei Immunsupprimierten auf [100]. Ein HIV-Test vor Behandlungsbeginn sollte mit dem Patienten besprochen werden.…”
Section: Durch Subgenus Vianniaunclassified